The Street-Smart Side of Business : A Behind-The-Scenes Guide to Inspire Forward Thinking. - Acosta, Tara. (Business Expert Press, 2021)
This book provides realistic insight as to what running a business is really about. It will help prepare you for all aspects of business and teach you how to protect yourself and your investment. The simplicity of using our intuition is often overlooked. The point is to understand exactly what you're getting into and not be blinded by the appearance of a good opportunity. This book will open your eyes and show you how to evaluate opportunities, people, and motives-skills often overlooked but are critical aspects of owning and operating a successful business. Prepare to get in tune with your "street smarts" in order to be successful in business and in life.